Following the Turnover of Soil Bioavailable Phosphate in Mediterranean Savanna by Oxygen Stable Isotopes. Issue 6 (8th June 2018) - Weiner, T.; Gross, A.; Moreno, G.; Migliavacca, M.; Schrumpf, M.; Reichstein, M.; Hilman, B.; Carrara, A.; Angert, A.
Abstract: Soil phosphate oxygen isotope analysis (δ 18 OP ) emerges as an effective method to trace the cycling of phosphorus (P) in soils. This study uses δ 18 OP measurements to learn how the nutrient status (P and N) affects the biological turnover rates of P in the soil of a Mediterranean holm oak Savanna. Such ecosystems cover >3 × 10 6  ha at the Iberian Peninsula. The analysis was part of a large‐scale nutrient manipulation experiment, where N and P were added. We followed the changes in δ 18 O values of soil bioavailable P during incubation of soils with a pulse of P and in addition measured the δ 18 OP in soil sampled at the site. In the incubations, the δ 18 OP values changed from the original value of the added P and approached a steady state of 16.3‰, which is 3.8‰ higher than the isotopic equilibrium with water. The steady state was higher with 18 O‐enriched incubation media water. The change in δ 18 OP values was more pronounced under trees, indicating a faster microbial P turnover rate. Incubation of soils fertilized with either P or N showed faster P turnover rate than control, implying N and P colimitation. Soil samples from P‐fertilized plots displayed higher δ 18 OP than the fertilizer, rather than the expected decrease toward steady‐state values, found at the control and N plots. The microbial P turnover rates during incubations were slower than the rates reported for lowland tropical forest with lower bioavailable P concentrations but resemble ecosystems with similar concentrations. Plain Language Summary: Phosphorus is an essential element for all forms of life. Due to retention by soil organic matter and minerals, most of it is unavailable for plant use, which makes it a limiting factor to plant growth in many ecosystems. In nature, phosphorus is bound to four atoms of oxygen that can have different masses. This bond can be broken only by enzyme‐mediated reactions. That allows us to use the different compositions of the oxygen as a means of distinguishing different phosphorus sources. In this study, we used it in order to learn how fertilization with phosphorus or nitrogen affects the rate in which phosphorus is consumed and released by soil microorganisms, in a Mediterranean savanna of scattered oak trees in Spain. We compared the phosphorus amounts and the oxygen atoms compositions in fertilized versus unfertilized plots by soil incubation with a phosphorus pulse and by measuring the change in those parameters. The uptake and release was faster beneath trees than in grassy areas and in fertilized plots with either phosphorus or nitrogen than in the unfertilized plots (implies colimitation to plant growth). The uptake and release rates were slower than rates found for tropical forest but similar to other Mediterranean sites. Key Points: Phosphate oxygen isotope measurements during soil incubation indicated faster microbial turnover of phosphate under tree canopies These measurements also show faster phosphate turnover in plot fertilized with nitrogen or phosphorus implying colimitation Phosphate turnover rates at this site were slower than the rates reported for lowland tropical forest but similar to other Mediterranean sites